The self‐reported health status of prisoners in New South Wales - T. Butler; A. Kariminia; M. Levy; M. Murphy (Elsevier, 2004)
Abstract Objective:To describe the physical health of the New South Wales prisoner population. Design:Cross‐sectional random sample of adult men and women prisoners. Setting:29 New South Wales correctional centres (27 male and two female). Participants:747 men and 167 women. Main results:Despite the comparatively young population, 81% of women and 65% of men had at least one chronic health condition; 41% of men and 59% of women reported multiple health problems. The most common conditions were back problems, poor eyesight, arthritis, high blood pressure and asthma. Chronic conditions were more prevalent among women prisoners. Thirty‐seven per cent of women and 28% of men rated their health as either 'poor' or 'fair' compared with 16% of women and 15% of men in the general NSW community. Psychiatric medication was more commonly prescribed to women than men (25% vs. 13%;p<0.001). Similarly, methadone maintenance was more common among women than men (39% vs. 13%; p<0.001). Conclusion:Men and women prisoners in NSW have multiple chronic health conditions. While not desirable, incarceration presents an opportunity to initiate treatment to improve the health of this disadvantaged group.